COMPARISON AND DIFFERENCES OF SHIRKAH JURISPRUDENCE AMONG MADHAB SCHOLARS - Dheddy Abdi Tamba; Yusdi Gozaly, Ahmad (Fakultas Hukum Universitas Djuanda, 2024)
hirkah is cooperation between two or more people in business, the profits and losses of which are borne jointly. In Uqud syirkah it is divided into five types, of which the Hanafi school of thought allows these five forms of syirkah, while the Maliki school of thought states that only three types of syirkah are valid, then the Syafii school of thought only allows two types of syirkah, and the Hambali school of thought only allows four types of syirkah. The differences in opinion of scholars regarding the types and laws of syirkah are due to several factors; namely differences in linguistic understanding abilities, differences in assessment of the status of hadith. Each school of thought scholar has his own method of ijtihad and school of thought recommendations, and of course this results in differences in the jurisprudential laws they conclude. This can be seen from the results of the legal products, which are also different between the jurisprudential laws issued and the legal products of other schools of jurisprudence. Cooperatives are a form of manifestation of syirkah whose legal basis is permissible according to Islamic (law), as long as it does not conflict with sharia principles (does not contain maysir, gharar and usury). This research discusses the halal and falsehood of cooperatives from the ulama Taqiyudin An Nabhani, according to the view of Taqiyyuddin An-Nabhani in his book, legal cooperatives are false with the term al-Jam'iyyah al-Ta'awuniyyah, because their operations are contrary to sharia principles.